An SECM‐Based Spot Analysis for Redoxmer‐Electrode Kinetics: Identifying Redox Asymmetries on Model Graphitic Carbon Interfaces. Issue 2 (29th December 2022) - Gaddam, Raghuram; Sarbapalli, Dipobrato; Howard, Jason; Curtiss, Larry A.; Assary, Rajeev S.; Rodríguez‐López, Joaquín
Abstract: The fundamental process in non‐aqueous redox flow battery (NRFB) operation revolves around electron transfer (ET) between a current collector electrode and redox‐active organic molecules (redoxmers) in solution. Here, we present an approach utilizing scanning electrochemical microscopy (SECM) to evaluate interfacial ET kinetics between redoxmers and various electrode materials of interest at desired locations. This spot‐analysis method relies on the measurement of heterogeneous electron transfer rate constants ( kf or kb ) as a function of applied potential (E−E 0 ′). As demonstrated by COMSOL simulations, this method enables the quantification of Butler‐Volmer kinetic parameters, the standard heterogeneous rate constant, k 0, and the transfer coefficient, α . Our method enabled the identification of inherent asymmetries in the ET kinetics arising during the reduction of ferrocene‐based redoxmers, compared to their oxidation which displayed faster rate constants. Similar behavior was observed on a wide variety of carbon electrodes such as multi‐layer graphene, highly ordered pyrolytic graphite, glassy carbon, and chemical vapor deposition‐grown graphite films. However, aqueous systems and Pt do not exhibit such kinetic effects. Our analysis suggests that differential adsorption of the redoxmers is insufficient to account for our observations. Displaying a greater versatility than conventional electroanalytical methods, we demonstrate the operation of our spot analysis at concentrations up to 100 mM of redoxmer over graphite films. Looking forward, our method can be used to assess non‐idealities in a variety of redoxmer/electrode/solvent systems with quantitative evaluation of kinetics for applications in redox‐flow battery research. Abstract : A ferrocene riddle . An SECM method to determine kinetic parameters on small regions of electrodes for flow battery applications is described. Surprisingly, SECM reveals kinetically limited electron transfer behavior for the reduction of ferrocenium (Fc + ) to ferrocene (Fc) on carbon electrodes in non‐aqueous solvents. Pt electrodes and aqueous solvents do not exhibit such asymmetric behavior.